2011
DOI: 10.1002/ca.21192
|View full text |Cite
|
Sign up to set email alerts
|

Topography of the recurrent laryngeal nerve in relation to the thyroid artery, Zuckerkandl tubercle, and Berry ligament in Kenyans

Abstract: Injury to the recurrent laryngeal nerve (RLN) is an important but avoidable complication of thyroidectomy. This complication may be avoided by the identification of the nerve facilitated by important landmarks found along its course. The setting for this work is the Human Anatomy Laboratory of the University of Nairobi. The aim of this work is to determine the topographic relationship of the RLN with the inferior thyroid artery (ITA), the tubercle of Zuckerkandl (TZ), and the ligament of Berry (LB) in a Kenyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 48 publications
3
46
0
8
Order By: Relevance
“…Steinberg et al [44] reported that the RLN courses in the neck between the branches of the inferior thyroid artery in about 6.5% of individuals, posterior to the inferior thyroid artery in 61.5% of individuals, and anterior to the inferior thyroid artery in 32.5%. On the right-hand side, the RLN may be in any of three locations in relation to the artery [44] (Figure 8), but in the majority of cases (45%), the RLN is superficial (dorsolateral) to the Berry's ligament [47]. The distal end of the RLN can be seen along the tract of the tracheoesophageal groove [30].…”
Section: Innervation Of the Thyroid Glandmentioning
confidence: 99%
“…Steinberg et al [44] reported that the RLN courses in the neck between the branches of the inferior thyroid artery in about 6.5% of individuals, posterior to the inferior thyroid artery in 61.5% of individuals, and anterior to the inferior thyroid artery in 32.5%. On the right-hand side, the RLN may be in any of three locations in relation to the artery [44] (Figure 8), but in the majority of cases (45%), the RLN is superficial (dorsolateral) to the Berry's ligament [47]. The distal end of the RLN can be seen along the tract of the tracheoesophageal groove [30].…”
Section: Innervation Of the Thyroid Glandmentioning
confidence: 99%
“…Depuis sa première description en 1867 comme étant la corne postérieure de la thyroïde par le chirurgien allemand Otto Wilhelm Madelung [1] et son étude anatomique par l'australien Émile Zuckerkandl [1] qui lui en a donné son nom, le TZ a fait l'objet de nombreux travaux [3][4][5][6][7]. Le point commun de toutes ces études est l'étude des rapports entre ce tubercule et le NLI.…”
Section: Discussionunclassified
“…La connaissance de ces rapports est d'un intérêt majeur en chirurgie, car elle permet de découvrir le NLI lors d'une thyroïdectomie, d'éviter sa lésion responsable de troubles vocaux et de séquelles fonctionnelles graves. En dehors d'une série kenyane [4] qui a étudié la présence du TZ en Afrique Orientale, à notre connaissance, aucune étude africaine n'a recherché et confirmé la présence de cette excroissance thyroïdienne en Afrique Sub-Saharienne. Notre étude semble être le premier travail réalisé sur la présence du TZ sur la thyroïde dans la sous-région ouest-africaine.…”
Section: Discussionunclassified
“…In a systematic review and meta analysis of 32 papers with 8655 recurrent laryngeal nerve sides assessing for the anatomic variation of the nerve relative to the inferior thyroid artery, Ling et al found the nerve to anterior (type A) in 20%, in between the branches (type B) in 28% and posterior(type C) in 52% of the cases (1). These findings are reflected in a local dissection study by Kaisha et al which was included in the Meta analysis by Ling et al (3). In the same systematic review, the authors reviewed 21 articles with 38,568 recurrent laryngeal nerve sides searching for a nonrecurrent laryngeal nerve as a variation.…”
Section: Anatomic Variationsmentioning
confidence: 98%
“…These variations can occur in the pattern of division, relations of the nerve to the inferior thyroid artery and its branches and the existence of the nerve in a non-recurrent fashion (1)(2)(3). It is worth noting that up to 28 variations have been described in anatomy studies (2).…”
Section: Anatomic Variationsmentioning
confidence: 99%